Model Pengaruh Influencer Endorsment dan Testimoni Pelanggan Terhadap Keputusan Pembelian pada Produk Fashion Lokal di Kota Bandung - Zikra Muhamad Filah; Halimah Zahrah (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The development of social media has driven changes in marketing strategies, particularly through the use of influencer endorsements and customer testimonials as a means of building consumer trust in the local fashion industry. Although these strategies are increasingly implemented, previous studies have shown inconsistent findings regarding their influence on consumers’ purchasing decisions. Therefore, this study aims to analyze the effect of influencer endorsements and customer testimonials on purchasing decisions for local fashion products in Bandung City. This study employs a quantitative approach with a causal research design, involving a sample of 154 respondents selected using purposive sampling. Data were collected through an online questionnaire using a Likert scale and analyzed using multiple linear regression with the assistance of SPSS version 26. The results indicate that influencer endorsements and customer testimonials have a positive and significant effect on purchasing decisions, both partially and simultaneously. These findings provide practical implications for local fashion businesses in designing more effective social media–based digital marketing strategies